Perancangan Inverter Satu Fasa PWM dengan Teknik Eliminasi Harmonisa - Barqie Tauhid . (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2014)
Abstract - Today, the development of technology continues to increase , it is seen more and more electronic equipment used in everyday use , one of them in the realm of science electrical energy conversion , ie the inverter . Inverters are variable voltage electrical appliance which can change DC power into AC power. There have been many studies conducted in order to obtain an output voltage of the inverter is sinusoidal wave . However, a new technique in rigorous academics UNTAN not been realized in the form of real inverter device . Harmonic elimination technique is a signal processing technique to get the inverter switching pattern in order to obtain the maximum output waveform THD sinusodal and minimum values ​​. With the combination of the control signal generating circuit and microcontroller AT89S52 LC filter , the inverter output is expected to have a sinusoidal waveform. From the results of the testing that has been done , harmonic elimination technique can be used to obtain a sinusoidal voltage with a total harmonic distortion is 9.1% . Keywords - Inverter , Harmonic Elimination technique , the control signal generating circuit microcontroller AT89S52 , LC Filters